Application real options infrastructure projects - Cheah, Charles Yuen Jen. (2008)
In all large engineering and infrastructure projects, valuation constitutes an important step during the initial stage as each stakeholder assesses the prospect of his/her investment. The complexity of valuation increases dramatically in the face of uncertainty especially when the risks are dynamic and stochastic in nature. To react to these uncertainties, project stakeholders and managers often changes their strategy of operation along the way as new information arrives. Conventional valuation methods, such as the Net Present Value (NPV) or Discounted Cash Flow (DCF) methods, often fail to capture the value of such operational flexibility. This results in an inaccurate assessment of the value of a project to a particular stakeholder.